PERAN LINGKUNGAN KERJA MEMODERASI PENGARUH MOTIVASI DAN DISIPLIN TERHADAP KINERJA GURU SEKOLAH DASAR SE-KECAMATAN TERSONO KABUPATEN BATANG - Moh Khuzaeni, 12.5202.0102; Susilowati, Yeye (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study aimsto analyze the Moderating Role of Work Environment Influence Motivationand Disciplineto Performance Primary Teachers through out the District Tersono Batang. In this study population  of all primary  schooll teachers in the District Tersono PNS, where assamples  takenas many as 165 people as respondents to the census technique. Measurementsusinga Likert scaleof 5 (five) alternative answers. Testinstrumentsused arevalidity and reliability. While thetestmodel usedisthe coefficientof determinationandF test(goodnes of Fit). Testthis hypothesisusingregressionanalysis. Based onthe results ofthe studycan be summarized asfollows: (i) Work Environmentis notimpactonteacher performance, (ii) Work Environmentmoderatinginfluence ofmotivationonteacher performance, (iii) Work EnvironmentWorkDisciplinemoderatinginfluenceon theTeacher Performance. Keywords: Motivation, Discipline, Work EnvironmentandTeacher Performance.